2018
DOI: 10.1101/414839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fate Before Function: Specification of the Hair Follicle Niche Occurs Prior to its Formation and Is Progenitor Dependent

Abstract: Cell fate transitions are essential for specialization of stem cells and their niches, but the precise timing and sequence of molecular events during embryonic development are largely unknown. Here, we show that dermal condensates (DC), signaling niches for epithelial progenitors in hair placodes, are specified before niche formation and function. With 3D/4D microscopy we identify unclustered DC precursors. With population-based and single-cell transcriptomics we define a molecular time-lapse of dynamic niche … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 105 publications
(149 reference statements)
0
0
0
Order By: Relevance
“…Previous RNA-seq profiling of E14.5 back skin has indicated that Rspo1 and Rspo3, but not Rspo2 and Rspo4, are expressed in the mesenchyme (Sennett et al, 2015;Mok et al, 2019;Snippert et al, 2010). We first analysed the expression pattern of Rspo1 and Rspo3 in the back skin prior to hair follicle induction (E12.5), during hair follicle induction (E13.5), and at placode stage (E14.5) by RNA in situ hybridization.…”
Section: Rspo1 Signalling Alone Is Insufficient To Induce Hair Follic...mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous RNA-seq profiling of E14.5 back skin has indicated that Rspo1 and Rspo3, but not Rspo2 and Rspo4, are expressed in the mesenchyme (Sennett et al, 2015;Mok et al, 2019;Snippert et al, 2010). We first analysed the expression pattern of Rspo1 and Rspo3 in the back skin prior to hair follicle induction (E12.5), during hair follicle induction (E13.5), and at placode stage (E14.5) by RNA in situ hybridization.…”
Section: Rspo1 Signalling Alone Is Insufficient To Induce Hair Follic...mentioning
confidence: 99%
“…As a result, epithelial keratinocytes migrate centripetally to form a thickening, the placode (Ahtiainen et al, 2014). Inductive signals from the placode then induce the underlying fibroblasts to migrate and aggregate underneath the placode, forming the mesenchymal component of the hair follicle, the dermal condensate (DC) (Glover et al, 2017;Biggs et al, 2018;Gupta et al, 2019;Mok et al, 2019). Subsequently, secondary inductive signals from the DC promote invagination of the epithelium to the mesenchyme, and the DC is engulfed by the epithelium and remains an integral part of the mature hair follicle, named the dermal papilla (DP) (Sennett & Rendl, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations